The Impact of Government Capital Assistance, Financial Literacy, and Business Innovation on the Profitability of Small and Medium Industries (IKM) in Palu City - Aulia Rizky Amalia; Sastrawan Farid, Erwan; Munawarah; Putri Utami, Ayu (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of government capital assistance, financial literacy, and business innovation on the profitability of small and medium industries (SMIs) in Palu City. Using a quantitative approach, data were collected from 37 SMI owners through structured questionnaires and analyzed using multiple linear regression. The findings show that government capital assistance and business innovation significantly improve profitability, while financial literacy has a positive but insignificant effect. Collectively, the three variables explain 73.3% of profitability variance. The results highlight the importance of integrating non-cash capital support with innovation-oriented programs to strengthen SMI profitability and sustainability.